AL-Hisbah: ALTERNATIVE ESCORT OF MODEN ARRANGEMENT - Abu Yazid, Afifah; Aziz, Bashir Ahmad (Universitas Islam Negeri Alauddin Makassar, 2015)
Control in management involves all aspects such as design (planning), preparation (structure), leadership (leadership), process of making decision (decision making), expenditure (productivity) and marketing (marketing). This paper takes some major issues, especially the role that should be filled by hisbah in the management, among them; limitations sense in controlling human such as judge productivity and accomplishment could be done but assessed behind the sense such as fraud, discrimination, corruption of quality, fraud, damage the mandate and etc, rather complex and it is not realized by human. Environments change, and humanity organizations can not inevitable that eventually will lead to various fraud problems in the organization, corruption and various problems are the effects of progress. The highest structure in the organization, employer or employee act to oversee all aspects in management, but the problem in the context is who will control the high employer in the organization? Based on the number of issues and problems, this study which is based on grounded theory will try to analyze the rule of hisbah which has been practiced since the time of the Prophet and his ccompanions as a systematic model to oversee the human signs in the organization management. Control in management is not only devoted the ability of human sense but also the role of religion is even more important to ensure the concept of control which will reach the maxima stage as defined. The function of control in fact is the continuous and it is not seasonal, because the movement of people and the organization process was always evolving. Then the job of controller is to justify the mistakes and misappropriation from time to time, it is necessary to be done with full justice and responsibilities. This situation requires effective control, refer to syariat.